Bulk intrinsic heterogeneity of metallic glasses probed by Meissner effect. (April 2020) - Li, Shubin; Lan, Fujun; Chen, Songyi; Peng, Di; Fang, Yuankan; Wang, Ren-Shu; Lou, Hongbo; Zhang, Xin; Zeng, Zhidan; Chen, Xiao-Jia; Qian, Dong; Zeng, Qiaoshi
Abstract: Structural heterogeneity has been proposed as a key intrinsic feature and mechanism underline unique properties and dynamic behavior of metallic glasses; however, it is still challenging in precisely describing and effectively characterizing the atomic-scale heterogeneity in metallic glasses. In this work, we employed the Meissner effect of superconductivity in magnetic susceptibility measurements as a sensitive bulk probe and successfully revealed the three-dimensional structural heterogeneity and its two-way evolution tuned by structural aging or rejuvenation in a La-based metallic glass. Compared with the resistivity measurements which only signal the most superconductive loop in inhomogeneous materials, the diamagnetic susceptibility signal of the Meissner effect maps the volumetric distribution of all superconductive regions and the corresponding structural heterogeneity in metallic glasses with high sensitivity. The experimental results reported in this article can be well interpreted based on a structural model of tunable "soft liquid-like" regions with soft vibration modes mixed with "hard solid-like" regions, validating the heterogeneity models of metallic glasses with new experimental data and approach. Highlights: The Meissner effect can be used to uncover the intrinsic structural heterogeneity in superconductive metallic glasses. The heterogeneity degree and volumetric distribution of metallic glasses can be estimated by the diamagnetic susceptibility. The diamagnetic susceptibility is susceptible to structural changes caused by aging or rejuvenation of metallic glasses.